Hi,

I have this equation and I need to solve for m... could someone please please help me??

A - m*B = (n*A - m*C) / (1+R)

(Itwasntme)

Printable View

- Nov 14th 2008, 12:30 PMcupcakesolving an equation
Hi,

I have this equation and I need to solve for m... could someone please please help me??

A - m*B = (n*A - m*C) / (1+R)

(Itwasntme) - Nov 14th 2008, 12:58 PMMath_Helper
Attachment 8698

(Talking)(Hi) - Nov 14th 2008, 01:22 PMmasters
Well, let's see...

$\displaystyle A-mB=\frac{(nA-mC}{1+R}$

$\displaystyle A(1+R)-mB(1+R)=nA-mC$

$\displaystyle -mB(1+R)=nA-mC-A(1+R)$

$\displaystyle -mB(1+R)+mC=nA-A(1+R)$

$\displaystyle mB(1+R)-mC=A(1+R)-nA$

$\displaystyle m(B(1+R)-C)=A(1+R)-nA$

$\displaystyle m=\frac{A(1+R)-nA}{B(1+R)-C}$

I checked over this once and didn't see any errors. I hope I didn't overlook anything. I also see that math_helper has already attached a solution. I see it is equivalent to my own. Take your choice. - Nov 14th 2008, 11:50 PMcupcake
thanks alot both of you!! :)